Mobile-Based Development of Meeting Room Management Application at PT.Jiwalu Studio - eko Haryadi; Dinda Maelani; Diah Wijayanti; Dewi Yuliandari; Indria Widyastuti (Universitas Islam Kuantan Singingi, 2021)
The role of technology greatly helps human life in completing its activities faster. PT. Jiwalu Studio Karawang has begun to use technology, for example, such as online-based attendance with a mobile application. Besides that, there are also activities that have not utilized technology, namely meeting or meeting activities. To use a meeting room, employees must first ask the room administrator about the availability of a meeting room. The meeting room agenda that day will be recorded by the administrator through the meeting agenda book. From the process of borrowing the meeting room, it was deemed too time and energy consuming because everything was done through the administrator. Therefore, development a meeting room management mobile application is created which is expected to be a solution for all employees. In developing this meeting room management application using Prototype method. This method is in accordance with the problems that occur, developers and users will be able to communicate with each other during the system design process